Vaccine confidence: the keys to restoring trust - Selim Badur; Martin Ota; Serdar Öztürk; Richard Adegbola; Anil Dutta (Taylor & Francis Group, 2020)
During the 20th century, the discovery of modern vaccines and ensuing mass vaccination dramatically decreased the incidence of many infectious diseases and in some cases eliminated them. Despite this, we are now witnessing a decrease in vaccine confidence that threatens to reverse the progress made. Considering the different extents of low vaccine confidence in different countries of the world, both developed and developing, we aim to contribute to the discussion of the reasons for this, and to propose some viable scientific solutions to build or help restore vaccine confidence worldwide.